SOME VIEWS ON THE TOPIC OF HYPOCORISMS AS THE VOCATIVE FORM IN ENGLISH AND UZBEK - Khalilova, Tabassum (Educational Research in Universal Sciences, 2023)
This article focuses on using hypocorism as vocative forms in the English and Uzbek languages. Hypocorisms are used when the speaker and listener are known each other. Especially, hypocorisms are used among relatives, family members and friends to call or address. While calling or addressing to someone or something, the hypocorisms are used as vocatives.